2006
DOI: 10.1124/dmd.106.009498
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cyp1a and Cyp2-Mediated Arachidonic Acid Epoxygenation and Suppression of 20-Hydroxyeicosatetraenoic Acid by Imidazole Derivatives Including the Aromatase Inhibitor Vorozole

Abstract: ABSTRACT:Cytochrome P450 (P450) enzymes metabolize the membrane lipid arachidonic acid to stable biologically active epoxides [eicosatrienoic acids (EETs)] and 20-hydroxyeicosatetraenoic acid (20-HETE). These products have cardiovascular activity, primarily acting as vasodilators and vasoconstrictors, respectively. EET formation can be increased by the prototype CYP1A or CYP2 inducers, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) or phenobarbital (PB), respectively. We report here that imidazole derivative drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
3
17
1
Order By: Relevance
“…20-HETE (ω), essentially the sole P450 aa product in livers of control CE, was suppressed by TCDD treatment in mitochondria, as previously observed in microsomes [12,13], here by means of 27.5 ± 2% in microsomes and 25 ± 8% in mitochondria (p = 0.001 and 0.045, respectively; n = 3).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…20-HETE (ω), essentially the sole P450 aa product in livers of control CE, was suppressed by TCDD treatment in mitochondria, as previously observed in microsomes [12,13], here by means of 27.5 ± 2% in microsomes and 25 ± 8% in mitochondria (p = 0.001 and 0.045, respectively; n = 3).…”
Section: Resultssupporting
confidence: 80%
“…TCDD has been found to suppress formation of 20-HETE in mammalian and avian liver microsomes [12,13] and is shown here also to suppress 20-HETE in mitochondria. Notwithstanding the dominant role of 20-HETE as virtually the only constitutive P450 product in CE liver microsomes and mitochondria, hepatic effects of 20-HETE are unknown.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, Bui et al (2012) also reported that TCDD increased 20-HETE in vivo in mouse liver. The finding also seems to contradict the substantial evidence that AHR activation by diverse agents, including TCDD, b-naphthoflavone, planar PCBs, and imidazole drugs, suppresses hepatic 20-HETE formation by microsomes in in vitro experiments in many species, including chick embryo, mouse, scup, rats, and guinea pigs (Huang and Gibson, 1991;Nakai et al, 1992;Lee et al, 1998;Schlezinger et al, 1998;Diani-Moore et al, 2006b) (also see Fig. 1).…”
Section: Discussioncontrasting
confidence: 39%
“…CYP2B (avian 2H) arachidonic acid epoxygenases are induced by phenobarbital, an activator of different nuclear receptors, i.e., constitutive androstane receptor (CAR) and the pregnane X receptor (PXR) (Nakai et al, 1992;Gilday et al, 1996;Gannon et al, 2000;Willson and Kliewer, 2002;Diani-Moore et al, 2006a;Rifkind, 2006). Imidazole-based drugs (i.e., vorozole, omeprazole, benzylimidazole) increase arachidonic acid metabolism by mixed induction of CYP1 and CYP2 family P450s (Diani-Moore et al, 2006b). Significantly, the different P450 epoxygenases all produce the same arachidonic acid products: four regioisomeric epoxides, 5,6-, 8,9-, 11,12-, and 14,15-epoxyeicosatetraenoic acids, and terminal hydroxyeicosatetraenoic acids (HETEs), i.e., 16-19 HETE (Capdevila et al, 1981), although the relative amounts of the products can vary for different P450s.…”
Section: Introductionmentioning
confidence: 99%